Seamless low-temperature thermochronological modeling in Andino 3D, towards integrated structural and thermal simulations. (January 2021) - Cristallini, Ernesto; Sánchez, Francisco; Balciunas, Daniel; Mora, Andrés; Ketcham, Richard; Nigro, Joaquín; Hernández, Juan; Hernández, Roberto
Abstract: We present the development of thermochronological tools for Andino 3D® software, that integrates Fetkin (Finite Element Temperature Kinematics). These tools allow the user to work on both the structural and the thermochronological model at the same time, providing a user-friendly environment that overcomes the need to work with different programs. Thermochronological and structural models can be checked and eventually corrected in a visual and intuitive form by following a 4-step workflow. The first step of such workflow is to define the thermochronological computing grid, checking in real time, if the resolution and coverage are satisfactory. After that, the interpolation process can be done, whereby velocity vectors for all nodes in beds and faults are calculated for all interpolated times. The third step of the workflow consists of filling thermal properties and velocities for all grid cells. The final step is the calculation of the thermal state at each time in the reconstruction. Boundary conditions (basal temperature, basal heat flow, surface temperature and altitude gradient) are defined by mouse picking as constant, spatially varying, time varying or spatially and time varying. To check the feasibility of a structural model, thermochronological samples can be defined at desired positions to predict time-temperature variations. Simulated fission track ages, mean track lengths and age standard deviations can be calculated for different minerals (apatite and zircons). Also, cooling ages and %Ro can be simulated for (U–Th-Sm)/He and vitrinite systems, respectively. The Carohuaicho structure in the southern Bolivia sub-Andean Ranges is presented as a case of study to demonstrate these tools. Andino 3D® allowed us to successfully simulate the t-T paths of four samples where (U–Th-Sm)/He measurements were available. The different models performed permitted us to conclude that a low geothermal gradient was likely to be present during the last 7 Ma of Andean deformation in the study region. Highlights: Andino 3D – Fetkin integration provides the user an all-in-one program where thermochronological and structural models can be done. Simulated fission track ages, (U–Th-Sm)/He ages and vitrinite %Ro can be simulated for samples positions in Andino 3D. Andino 3D simulation of Carohuaicho structure in Bolivian Subandean is in agreement with low geothermal gradient, (<30°C/Km) for the last 7 Ma.